IN VITRO CULTIVATION OF RUBUS SANCTUS SCHREB. - VÃ¢ntu, Smaranda (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The plants are a major source of natural products used as pharmaceuticals, agrichemicals. Most likely plants will continue to provide novel natural products as well as chemical models for new drugs. In vitro biology and technology have been proposed as contributing toward production of plant natural products, via micropropagation, cell culture (1, 2, 3). The paper studies “in vitro”behaviour of Rubus sanctus Schreb., a native of Central Asia, used in traditional medicine. It were tested, not only the dedifferentiation capacity, but also the regenerative potential for rapid micropropagation.The initiation of in vitro cultures at Rubus sanctus Schreb was achieved from axillary buds, cultivated on different variants of Murashige-Skoog medium. The MS medium supplemented with benzylaminopurine stimulated the direct caulogenesis at Rubus sanctus Schreb., whereas the MS medium supplemented with kinetine generated an intensive proliferative reaction and callus development.The regeneration of whole plants was obtained in two steps: the shoots were excised and transferred to fresh medium and then rooting of these shoots was achieved on the same medium without growth regulators. References: 1.Ayoub, N.A., Hussein, S.A.M., Reiß, C., Mentel, R., Lindequist, V. (2004)- Phenolics of interesting antiviral and antibacterial activities from Rubus sanctus, Bull. Fac. Pharm. Cairo, 42(1): 223-2312.Connolly, J., Hill, R.A. (2005)- Triterpenoids, Nat. Prod. Rep. 22: 230-2483.Erdemoglu, Nurgun, Kupeli, Esra, Yesilada, Erdem (2003)-Anti-inflammatory and antinociceptive activity assessment of plants used as remedy in Turkish folk medicine, Journal of ethnopharmacology, 89: 123-129